From LP to Screen: Tito Schipa Jr.’s "Orfeo 9" (1973–1975) (Sound Stage Screen, 2024)
Broadcasted for the first time in 1975, Orfeo 9 is a film musical written and directed by Tito Schipa Jr. and produced for television by Rai, the Italian state broadcaster. The first Italian rock opera to appear on the TV screen, it is a modern version of the myth of Orpheus. Adapted from the theatrical musical staged in 1970 in Rome, the film is primarily a remediation of the double LP released in 1973: it was in fact built on the pre-existing audio recording, thus becoming the first experiment of “visualized soundtrack” on Italian television, according to critic Renato Marengo’s definition. Accordingly, this presentation reverses the common perspective that considers what pop music can bring to cinema, asking instead what the language of film can bring to a record.In particular, I focus on the ways in which the film Orfeo 9 contributed to the “shaping of the experience of song,” to quote film scholar Claudio Bisoni. I discuss the modalities of the “musical re-writing of the image” (Simone Arcagni) that allowed Schipa to experiment with different relationships between audio and video through the medium of cinema. The issue of genre, in particular the American film musical, plays a significant part in my analysis. My overall intention is to show how the film Orfeo 9 was an experiment that aimed at a synthesis between different possibilities of remediation of songs.
Keywords: Orfeo 9; Tito Schipa Jr.; Italian film musical; Italian rock opera; visualized soundtrack